EVALUASI PENYUSUNAN PERUBAHAN PERATURAN LKPP NO. 7/2021: PERSPEKTIF GOOD GOVERNANCE DAN KESESUAIAN NORMA - Nurhaliza Fairuz; Saifullah Zakaria; Selvi Centia (LPPM Universitas Abdurrab, 2025)
The drafting of the Amendment to LKPP Regulation No. 7/2021 faces challenges in harmonizing with national policies and regional human resource and institutional needs. This study analyzes the drafting process, evaluates the substance and technical suitability, and identifies obstacles and alternative efforts. This study employs a descriptive qualitative method, with data collected through literature review, documentation, participatory observation, and semi-structured interviews. Data analysis uses the interactive model of Miles and Huberman (1992) with the 5W1H approach, analysis of the principles of good governance of the UNDP (1997), and Ministry of Law and Human Rights Regulation No. 23/2018. The results of the study indicate that the principles of participation, transparency, accountability, and strategic vision have been optimally implemented, while legal certainty, effectiveness and efficiency, fairness, and consensus orientation remain weak due to the absence of an Inter-Ministerial Committee (PAK), power imbalances, substantive disharmony, and inconsistencies in drafting techniques. Efforts undertaken LKPP include the formation of the PAK, cross-unit task forces, and strengthening internal harmonization. This study emphasizes the need to strengthen cross-sectoral coordination and the completeness of supporting documents to ensure a systematic, effective, and legally compliant legal drafting process.